Abnormal Microstructural Development of the Cerebral Cortex in Neonates With Congenital Heart Disease Is Associated With Impaired Cerebral Oxygen Delivery - Kelly, Christopher J. (J Am Heart Assoc, 2019)
BACKGROUND: Abnormal macrostructural development of the cerebral cortex has been associated with hypoxia in infants with congenital heart disease (CHD). Animal studies have suggested that hypoxia results in cortical dysmaturation at the cellular level. New magnetic resonance imaging techniques offer the potential to investigate the relationship between cerebral oxygen delivery and cortical microstructural development in newborn infants with CHD. METHODS AND RESULTS: We measured cortical macrostructural and microstructural properties in 48 newborn infants with serious or critical CHD and 48 age‐matched healthy controls. Cortical volume and gyrification index were calculated from high‐resolution structural magnetic resonance imaging. Neurite density and orientation dispersion indices were modeled using high‐angular‐resolution diffusion magnetic resonance imaging. Cerebral oxygen delivery was estimated in infants with CHD using phase contrast magnetic resonance imaging and preductal pulse oximetry. We used gray matter–based spatial statistics to examine voxel‐wise group differences in cortical microstructure. Microstructural development of the cortex was abnormal in 48 infants with CHD, with regions of increased fractional anisotropy and reduced orientation dispersion index compared with 48 healthy controls, correcting for gestational age at birth and scan (family‐wise error corrected for multiple comparisons at P<0.05). Regions of reduced cortical orientation dispersion index in infants with CHD were related to impaired cerebral oxygen delivery (R (2)=0.637; n=39). Cortical orientation dispersion index was associated with the gyrification index (R (2)=0.589; P<0.001; n=48). CONCLUSIONS: This study suggests that the primary component of cerebral cortex dysmaturation in CHD is impaired dendritic arborization, which may underlie abnormal macrostructural findings reported in this population, and that the degree of impairment is related to reduced cerebral oxygen delivery.